DEVELOPMENT OF E-COMMERCE IN BUSINESS TRANSFORMATION IN THE DIGITAL ERA - Iqbal Arif Budiman; Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In the digital era, business transformation is unavoidable, especially with the emergence of e-commerce which has revolutionized the way companies operate and interact with consumers. This research aims to dig deeper into the development of e-commerce and its impact on the transformation of traditional businesses into digital. Through qualitative and quantitative approaches, this research collects data from various companies that have integrated e-commerce into their business operations, as well as consumers who are affected by this change. The research results show that e-commerce not only allows companies to reach a wider market and increase sales, but also drives innovation in marketing strategies, operational models and customer service. Furthermore, this research identifies the challenges companies face in the transition to digital, such as data security issues, increasing competition, and the need for rapid technological adaptation. The conclusions of this research suggest that to survive and thrive in the digital era, companies must implement effective e-commerce strategies, utilize the latest technology, and continue to innovate to meet consumers changing needs and expectations.